2011
DOI: 10.1186/1752-1947-5-257
|View full text |Cite
|
Sign up to set email alerts
|

Asystole following positive pressure insufflation of right pleural cavity: a case report

Abstract: IntroductionAdverse hemodynamic effects with severe bradycardia have been previously reported during positive pressure insufflation of the right thoracic cavity in humans. To the best of our knowledge, this is the first report of asystole during thoracoscopic surgery with positive pressure insufflation.Case presentationA 63-year-old Caucasian woman developed asystole at the onset of positive pressure insufflation of her right hemithorax during a thoracoscopic single-lung ventilation procedure. Immediate deflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These changes are more marked in right sided carbomediastinum than the left side as it is a low pressure chamber in the cardiovascular system [3][4][5][6][7][8][9][10][11][12][13]. In review literature, the American association of Gynecology reported an incidence of one in 2500 cases asystolic arrest during laparoscopy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are more marked in right sided carbomediastinum than the left side as it is a low pressure chamber in the cardiovascular system [3][4][5][6][7][8][9][10][11][12][13]. In review literature, the American association of Gynecology reported an incidence of one in 2500 cases asystolic arrest during laparoscopy [7].…”
Section: Discussionmentioning
confidence: 99%
“…One more case of asystole during laparoscopic Cholecystectomy has been described [8]. One case of asystole following positive pressure insufflation of right pleural cavity during hilar lymphadenectomy is also described [5]. But till date asystole during the robotic assisted thoracic surgery has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Use of CO 2 insufflation in RATS improves the field of vision by moving anatomical structures away from the field of view and reduces the incidence of camera fogging. Patient risks from CO 2 insufflation include hemodynamic changes such as decreased preload, hypotension, 1 increased central venous pressure, and increased pulmonary arterial pressure 15 ; and precipitation of hypercarbia and acidosis 16 …”
Section: Literature Reviewmentioning
confidence: 99%
“…hemodynamic changes such as decreased preload, hypotension, 1 increased central venous pressure, and increased pulmonary arterial pressure 15 ; and…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, insu ation of CO 2 creates physiologic effects similar to a tension pneumothorax. Acute changes of intrathoracic pressure during the initial insu ation of CO 2 can compromise cardiopulmonary function and patient safety [5][6][7]. Currently, few reports have observed the characteristics of intrathoracic pressure after arti cial CO 2 pneumothorax has been established and its potential impacts on cardiorespiratory function.…”
Section: Introductionmentioning
confidence: 99%